Phytogeographic aspects of transformation of the vascular plant flora in coastal mires exemplified by the eastern part of the Kashubian Coastal Region (northern Poland) - Budyś, Agnieszka (Biodiversity: Research and Conservation, 2006)
Mires in a coastal zone are distinct from the others because of presence of Atlantic and boreal species in their flora. During the last century far-reaching changes in peatland flora were observed. The aim of this research was to analyse the phytogeographical aspects of transformation of vascular plants flora in disturbed coastal mires. The research was conducted in a complex of mire habitats in the Kashubian Coastal Region. Long term anthropic pressure in this area caused significant changes in abiotic conditions as well as in the plant cover. Contemporary vascular flora was recorded between 2000 and 2004 and compared with all the data from former research. Groups of Atlantic and boreal species were characterized by their sociological and biological structure as well as local habitat amplitude. There were 32 boreal and 38 Atlantic taxa found within this area. Nowadays, ratio between them is slightly moved towards Atlantic species. The probable reason of this change is the anthropic transformation of environment, which caused enlargement of the area of dry mineral habitats, colonized by grasslands and heathlands species.